L’évolution du contrat social de la recherche universitaire: contraintes et opportunités - Landry, Rejean (Canadian Journal of Higher Education, 1995)
Ongoing mutations in the funding of university research lead to the intensification of the reflexions on the increasing interdependence linking the universities to the governments. Through the years, these linkages of interdependence have generated a sort of social contract that was initially implicit, but has become increasingly more and more explicit, including increasing number of provisions governing the linkages prevailing between the universities and the governments. The paper demonstrates that the provisions of this social contract have been gradually revised under the pressures of changes that gradually occurred concerning the views of the government policy makers and the needs and practices of university research. The examination of these changes incites the author to conclude that the social contract relating the universities to the governments will become more and more compelling. The last part of the paper proposes to consider these constraints in a positive manner in attempting to figure out opportunities opened for future funding of university research. Specific lines of lobbying actions are suggested to improve the marketing of university research.